Reimagining Medical Education Toward Antiracist Praxis (Mary Ann Liebert, 2023)
Medicine has a longstanding history of racism that promulgates existing health inequities. Current medical education, largely based on the biomedical framework, omits critical discourse on racism and White supremacy, which continue to harm individuals and communities of color. Such ahistorical and apolitical orientation inadequately trains learners to identify and address racism in clinical practice. Although curricula on racial health disparities, social determinants of health, cultural competency, and implicit bias have been operationalized by several medical schools, they do not identify the racism embedded in systems of care, nor do they provide transformative steps toward true health equity and justice. As such, this article proposes bold radical frameworks as the foundation for reimagining medical education in the United States. Founded on critical race theory, abolition, and decolonization, the authors provide a view of an antiracist medical education, one that highlights the history and legacy of racism in medicine and positions medical trainees and practicing physicians as active agents in medicine's antiracist transformation.